Kenneth G. Appold & Nelson H. Minnich (eds.), The Cambridge History of Reformation Era Theology (Cambridge: Cambridge University Press, 2024), pp. xiii + 792. ISBN 9781107044043 - Donnelly, Colin Michael (Journal of Anglican studies, 2025)
Kenneth G. Appold & Nelson H. Minnich (eds.), The Cambridge History of Reformation Era Theology (Cambridge: Cambridge University Press, 2024), pp. xiii + 792. ISBN 9781107044043. - Volume 23 Issue 1